DIFFERENCES IN THE PREVALENCE OF MOLAR-INCISOR HYPOMINERALIZATION BETWEEN URBAN AND RURAL AREAS - El Fitriyah, Rhabiah; Hartman, Henri; Putri Gunawan, Alvaezra (Fakultas Kedokteran Gigi Unjani, 2025)
Dental enamel defects are developmental anomalies commonly found in primary and permanent teeth. One of the developmental anomalies of enamel structure is the hypomineralization of molar and incisor teeth. Molar-Incisor Hypomineralization (MIH) is a localized autosomal recessive disease or amelogenesis imperfecta that may be associated with enamel-forming genes such as AMBN and TUFT1. The etiology of MIH can be attributed to prenatal, perinatal, and postnatal factors, such as low birth weight, antibiotic use, toxins from breastfeeding, infections during pregnancy, premature birth, birth complications, and a family history of enamel defects. This research is an observational analytical study with a cross-sectional design. The sampling technique used in this study is probability sampling, specifically simple random sampling in elementary school children in the urban area of Cimahi City and the rural area of West Bandung Regency.. The results of the study in the urban area of Cimahi City revealed 297 respondents, aged 8-12 years old, with a prevalence of MIH in the urban area (9.8%), indicating that 29 children experience MIH. In the rural area of West Bandung Regency, 293 respondents of elementary school children aged 8-12 years were included, showing a prevalence of MIH in the rural area (14.7%), indicating that 43 children have MIH. The research results indicate that the prevalence of MIH in rural areas is higher compared to the prevalence of MIH in urban areas, with a probability value of 0.069, which is greater than 0.05 (P>0.05). Therefore, statistically, it shows a non-significant difference in the prevalence of MIH between Cimahi City and West Bandung Regency. DOI : 10.54052/jhds.v4n3.p289-300